Chemical, functional, rheological and structural properties of broken rice–barnyard millet–green gram grits blend for the production of extrudates. (15th March 2023) - Nisha, R.; Nickhil, C.; Pandiarajan, T.; Pandiselvam, R.; Jithender, Bhukya; Kothakota, Anjineyulu
Abstract: Broken rice is an underutilized by‐product of the rice milling industry. It was added with green gram and barnyard millet to investigate as a source of nutrition‐based value‐added food product. The study was carried out to examine the influence of formulated composite flour obtained from broken rice ( Oryza sativa ) (50%–80%), barnyard millet ( Echinochloa esculenta ) (10%–30%), and green gram ( Vigna radiata ) (10%–30%) on the chemical properties, functional properties, pasting properties, oscillatory test, flour behavior, and microstructure of extrudate. The ash, crude fiber, crude protein, fat, and carbohydrate of the extrudate ranged from 1.62%–1.78%, 1.88%–2.43%, 13.47%–14.57%, 4.9%–7.48%, and 66.86%–70.8%, respectively. The water absorption index (WAI) and water solubility index (WSI) for the flour ranged from 5.06%–6.18 g/g and 2.34%–3.99%. The formulated composite flours having a higher percentage of broken rice showed significant differences ( p < 0.05) in their pasting properties, pasting temperature, peak viscosity, breakdown viscosity, and setback and final viscosity. The pasting properties gave better results using a twin‐screw extruder with operating conditions of barrel temperature of 110°C, screw speed of 290 rpm, and 14% moisture content (w.b.). The microstructure of the extrudate obtained from 80% broken rice, 10% barnyard millet, and 10% green gram grits flour possessed a more integrated, well‐defined porosity, indicating a completely gelatinized structure. Practical application: Determination of biochemical, structural, and rheological properties of ingredients are essential for the production desirable ready‐to‐eat snacks. In this context, the present study evaluated the functional and rheological properties of broken rice–barnyard millet–green gram blend for the production of nutritious snacks with desirable physical and textural properties. The findings of the study would be useful for food products industries using millets and broken rice as a major raw material. Abstract : Impact of rheological properties of composite flour on extrusion cooking was studied and characterized the functional properties of developed extrudates.